Stability Assessment of the PET-Based Distributed Grid - Huang, Kun; Chi, Fuhai; Dou, Zhenlan; Yang, Zhongguang; Fu, Ming; Liu, Cheng (Frontiers in Energy Research, 2022)
The penetration of renewables is getting higher nowadays. The traditional transformer can no longer meet the requirements of utilities. For this reason, power electronic transformer (PET) is proposed as one of the promising alternatives. However, there are coupling issues between PET and the connected converters in the low-voltage grid. To well study the issues, this paper develops impedance models of the PQ node, PV node and PET. Based on the models, the system stability under different scenarios is assessed by the generalized Nyquist criterion. The effects of the line impedance and control parameters on system stability are studied. Moreover, a comprehensive parameter sensitivity analysis is carried out to reveal the coupling mechanism between converters. Simulations are given to validate the effectiveness of the theoretical analyses.